PREDIKSI KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH PDAM DI KECAMATAN LUBUK BEGALUNG KOTA PADANG TAHUN 2027 - Irma, Irma Sapitri; Purwaningsih, Endah (JURNAL BUANA, 2025)
Abstract The purpose of this research is: 1) To determine the population projection in Lubuk Begalung District in the year 207. 2) To ascertain the demand for clean water in Lubuk Begalung District based on the projected population increase over the next 10 years.The research design employed in this study is Quantitative Descriptive. The data utilized consists of secondary data and secondary data encompassing population figures, PDAM customers, and clean water availability data in Lubuk Begalung District. The analytical technique employed includes the Population Projection Method, specifically the Arithmetic Method, to predict the population, along with the prediction of clean water demand in the year 2027.The outcomes of this study reveal that Lubuk Begalung District is experiencing a significant increase in population and is categorized as a "Medium City" for the next 10 years, reaching a total population of 136.896 by the year 2027. Calculations for domestik and non-domestik clean water demand in 2027 for Lubuk Begalung District amount to 234.43 L/second, with estimated water loss reaching 35.52 L/second. Furthermore, based on the population projection, it is determined that the number of people to be served by PDAM in 2027 will be 127,944, with a per capita water requirement of 213.12 L/day. The total water availability at PDAM Kota Padang is 47.328.357 m3/s. From this comparison, it can be concluded that the current water source availability is still capable of meeting the clean water demand in the Lubuk Begalung District area until 2027.